A cross-sectional survey of community pharmacists towards antimicrobial stewardship in Malaysia - Khan, Muhammad Umair; Ahmad, Amir; Abujabal, Hassali; Elkalmi, Ramadan Mohamed Mahmod (Elsevier Inc, 2016)
Objectives: Antimicrobial resistance is the most recognized public health problem worldwide. Injudicious use of antibiotics significantly contributes to this problem.Antimicrobials are amongst the most utilized drugs in Malaysia. Antimicrobial stewardship programs seek to optimize the use of antibiotics. Community pharmacists play an important role in executing these programs as they process medication orders and counsel patients on the appropriate use of antibiotics. The objective of this study was to assess the perceptions and practices of community pharmacists towards antimicrobial stewardship in Selangor, Malaysia. Methods: The study was conducted in Selangor, one of the most prosperous states in Malaysia. Selangor has a population of about 3.75 million, and the total number of registered community pharmacies in Selangor is 297. A cross-sectional study was conducted for the period of 2 months, using a self-administered, pre-tested questionnaire among randomly selected community pharmacists in Selangor, Malaysia. Results: A total of 225 participants were contacted to achieve a required sample size of 188 (response rate = 83.5%). The majority of the participants strongly agreed that the antimicrobial stewardship program is essential to improve patient care (96.8%). However, more than half of the pharmacists were neutral in their opinion about the incorporation of antimicrobial stewardship programs in community pharmacies (54.2%). Though collaboration was often done by the pharmacists with other health professionals over the use of antibiotics (n=104, 55.3%), a significant proportion of the participants (54.2%) rarely/occasionally participate in antimicrobial awareness campaigns. Qualification of the participants was significantly associated with the perceptions and practices of the respondents (p<0.05). While the experiences was the determining factor with respect to the perceptions of participants towards antimicrobial stewardship (p<0.05). Conclusions: The perceptions and practices of community pharmacists were positive towards antimicrobial stewardship. Further studies are warranted to validate these results by including community pharmacists from other states of Malaysia